Design of New Student Registration Information System at MTsN 4 Kab. Lima Puluh Kota Android Based Cities - Putri, Yulia Elsa; Derta, Sarwo (Knowbase : International Journal of Knowledge in Database, 2021)
There are still not many SMP/MTs/Equivalents in Indonesia holding online New Student Admissions, one example being MTsN 4 Kab. Lima Puluh Kota under the auspices of the Ministry of Religion Kab. Lima Puluh Kota. During manual PPDB at MTsN 4 Kab. Lima Puluh Kota there are several obstacles both experienced by the school, prospective students and parents, both in terms of administration or information at the time of PPDB implementation. Another problem that arises is the distance of the radius and distance of students who will register to school; from the data, the authors found that the radius and the furthest distance traveled by students was Â± 18-20. It is the author's background in designing an Android-based PPDB information system using the 4D version of the R&D method with the SDLC waterfall system development model. The programming language used is PHP language assisted with MySQL database. From the product test that the author did, the results obtained: the validity test was carried out by filling out a questionnaire that referred to the Aiken's V statistical formula, namely 0.80 Valid criteria addressed to 3 lecturers, the practicality test was carried out by filling out a questionnaire which was analyzed with a percentage per rhythm, namely 93 ,33 Very Practical criteria aimed at 3 teachers and the effectiveness test is carried out by filling out a questionnaire that refers to the statistical moment kappa formula, namely 0.91 Very Effective criteria addressed to 15 students.